An Approach to Secure Data Sharing in the Internet of Things Using Blockchain- Based Proxy Re-Encryption - Keshav Kumar, Choudhary; Shreedhara N, Hegde; C., Pui Lin (INTI International University, 2024)
The prevalence of data sharing has increased with the rise in popularity of cloud computing and the Internet of Things (IoT). However, ensuring data security is difficult because of the possible negative consequences of illegal data usage. This study presents a method for ensuring the secure transmission of data in cloud environments: proxy re-encryption. The identity-based encryption method enables data owners to transfer encrypted data to the cloud. Subsequently, a proxy re-encryption framework enables authorized individuals to access the data. To surpass the limitations of IoT device resources, we utilize an edge device as a proxy server to transfer computationally intensive tasks to a separate device. By utilizing the advantages of information-centric networking, we can optimize network capacity and enhance service quality by efficiently distributing cached content across the proxy. This method decreases bottlenecks in centralized systems while providing precise control over data access. The proposed work demonstrates the effectiveness of the strategy in ensuring data security, confidentiality, and integrity through thorough security research and plan review.